Fracture resistance of five intra-orifice barriers in endodontically treated mandibular premolars: an in vitro study - Yüksekkaya, İrfan; Aydın, Uğur; Burhan Çetinkaya, Oğuz; Çulha, Emre (Vojnosanitetski pregled, 2026)
Background/Aim. Endodontically treated teeth (ETT) are more prone to fractures than vital teeth, and insertion of an intra-orifice barrier (IOB) can increase their fracture resistance (FR). The aim of this study was to compare and evaluate the FR of ETT using smart dentin replacement (SDR), everX Flow (EXF), resin-modified glass-ionomer cements (RMGIC), calcium-enriched mixture (CEM), and universal flowable composite (UFC) as IOBs. Methods. After performing root canal treatment on 70 human mandibular premolars with a single root canal, the coronal 3 mm of root fillings were removed with heated instruments, except for the control specimens. Based on the IOB above the root canal obturation, the filled specimens were divided into six groups: RMGIC (n = 13), UFC (n = 13), SDR (n = 13), CEM (n = 13), EXF (n = 13), and a control group (CG; n = 5). A spherical steel insert with a diameter of 2 mm was used in the strength test with a universal testing machine. Data were analyzed using the Shapiro-Wilk test, analysis of variance, and least significant difference tests. The value of p < 0.05 is considered statistically significant. Results. The EXF group showed the highest mean FR of 759.9 ± 177.9 Newtons. The groups RMGIC, UFC, and EXF demonstrated a statistically significant difference compared to CG. CEM had a lower FR value than all groups except the SDR and CG. However, the FR of SDR was lower than that of the UFC and EXF groups. There were no significant differences between EXF, UFC, and RMGIC groups. Conclusion. Except for SDR and CEM, all other groups showed an increase in FR compared to CG. The results indicate that using EXF, UFC, or RMGIC as IOB can significantly enhance the FR of ETT compared to untreated controls. Clinically, selecting these IOBs may help prevent root fractures and improve the long-term prognosis of ETT.
Keywords: bicuspid; dental cements; endodontics; in vitro; materials testing; root canal preparation.